The Climate of Portugal - Mora, Carla (2021)
Portugal shows a Mediterranean climate with, predominantly, a wet cool season and a dry summer. Despite the concentration of the precipitation in winter, there is a high inter-annual variability, resulting from the latitudinal position in the south-western façade of Europe. The prevailing weather conditions are anticyclonic, with Portugal’s seasonality being marked by the influence of either the subtropical anticyclonic belt or the zonal circulation. Despite the relatively small area of the country, its geographical position in the interplay between the Atlantic and Mediterranean influences, as well as its relief differences, with mountainous north and central regions and a flatter south, generates a diverse mosaic of regional climates. In this chapter, we show the main climate characteristics of Portugal, followed by a brief presentation of the main climatic scenarios for the end of the twenty-first century. The chapter closes with a synthesis of the palaeoenvironmental evolution of Portugal since the last glacial stage.